2018
DOI: 10.1038/s41386-018-0150-5
|View full text |Cite|
|
Sign up to set email alerts
|

Isoform-selective phosphoinositide 3-kinase inhibition ameliorates a broad range of fragile X syndrome-associated deficits in a mouse model

Abstract: Defects in the phosphoinositide 3-kinase (PI3K) pathway are shared characteristics in several brain disorders, including the inherited intellectual disability and autism spectrum disorder, fragile X syndrome (FXS). PI3K signaling therefore could serve as a therapeutic target for FXS and other brain disorders. However, broad inhibition of such a central signal transduction pathway involved in essential cellular functions may produce deleterious side effects. Pharmacological strategies that selectively correct t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…Therapeutic value of correcting the altered PI3K-Akt-S6K1 signaling in FXS is strongly suggested by that genetic removal/reduction of S6K1, PIKE, and p110ß subunit of PI3K can rescue the elevated overall protein synthesis and multiple behavioral abnormalities in Fmr1 KO mice 18,28,35 . A more recent study showed that systemic injection of a novel p110β-specific inhibitor GSK2702926A, a similarly structured compound of which is under investigation in a cancer clinical trial, rescues cellular and behavioral abnormalities in Fmr1 KO mice 46 . To realize therapeutic value of targeting the PI3K-Akt-S6K1 signaling cascade, a significant advancement is to find a clinically suitable approach to effectively dampen PI3K-Akt-S6K1 activity in FXS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic value of correcting the altered PI3K-Akt-S6K1 signaling in FXS is strongly suggested by that genetic removal/reduction of S6K1, PIKE, and p110ß subunit of PI3K can rescue the elevated overall protein synthesis and multiple behavioral abnormalities in Fmr1 KO mice 18,28,35 . A more recent study showed that systemic injection of a novel p110β-specific inhibitor GSK2702926A, a similarly structured compound of which is under investigation in a cancer clinical trial, rescues cellular and behavioral abnormalities in Fmr1 KO mice 46 . To realize therapeutic value of targeting the PI3K-Akt-S6K1 signaling cascade, a significant advancement is to find a clinically suitable approach to effectively dampen PI3K-Akt-S6K1 activity in FXS.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of absolute efficacy is common for drugs used for complex neurological disorders. It is noticed that targeting ERK1/2 or PI3K by lovastatin, metformin, and GSK2702926A rescues some but not all symptoms 19,39,46 . Such limitation may be due to multiple pathological alterations in FXS; combinatorial targeting multiple disease factors represents an emerging idea to achieve more robust therapeutic outcome 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, treatment with S6K1 inhibition may be more beneficial by specifically targeting abnormal protein synthesis (47). Another recent study found that inhibition of the specific PI3K isoform p110β can ameliorate FXS behavioral symptoms (50), suggesting that specific inhibition of p110β-driven mTOR activity could also be more beneficial than inhibiting all mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic value of correcting the altered PI3K-Akt-S6K1 signaling in FXS is strongly suggested by that genetic removal/reduction of S6K1, PIKE, and p110ß subunit of PI3K can rescue the elevated overall protein synthesis and multiple behavioral abnormalities in Fmr1 KO mice 15, 39, 48 . A more recent study showed that systemic injection of a novel p110β-specific inhibitor GSK2702926A, a similarly structured compound of which is under investigation in a cancer clinical trial, rescues cellular and behavioral abnormalities in Fmr1 KO mice 49 . To realize therapeutic value of targeting the PI3K-Akt-S6K1 signaling cascade, a significant advancement is to find a clinically suitable approach to effectively dampen PI3K-Akt-S6K1 activity in FXS.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of “absolute efficacy” is common for drugs used for complex neurological disorders. It is noticed that targeting ERK1/2 or PI3K by lovastatin, metformin, and GSK2702926A rescues some but not all symptoms 40, 41, 49 . Such limitation may be due to multiple pathological alterations in FXS; combinatorial targeting multiple disease factors represents an emerging idea to achieve more robust therapeutic outcome 50 .…”
Section: Discussionmentioning
confidence: 99%